1980
DOI: 10.1002/1097-0142(19801101)46:9<2093::aid-cncr2820460931>3.0.co;2-4
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous regression of non-Hodgkin's lymphoma: A report of nine cases

Abstract: Seven previously untreated patients and two previously treated patients with advanced non-Hodgkin's lymphoma (Stages III and IV) and favorable histologic subtypes had spontaneous regression of their lymphomas. Regressions were either complete or partial and were frequently durable. Six of the seven patients who had spontaneous regression of their lymphomas prior to any therapy have yet to require treatment. Seven of the nine spontaneous regressions occurred in a group of 44 patients who were followed with init… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
52
0

Year Published

1983
1983
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 130 publications
(54 citation statements)
references
References 14 publications
2
52
0
Order By: Relevance
“…Indeed, the deterministic immunogenicity path can be summarised Moreover, since for many cases of tumour suppression in the case of low c tumour sizes do reach very large values, we must stress that in these cases the eradication is only theoretical since the host unfortunately dies. However, for larger values of c the tumour size is large but compatible with life, so that the model may contribute to a better understanding some sporadic cases of spontaneous permanent regression of macroscopic tumours (Krikorian 1980). Of course for large values of c the probability of having a remission is large (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the deterministic immunogenicity path can be summarised Moreover, since for many cases of tumour suppression in the case of low c tumour sizes do reach very large values, we must stress that in these cases the eradication is only theoretical since the host unfortunately dies. However, for larger values of c the tumour size is large but compatible with life, so that the model may contribute to a better understanding some sporadic cases of spontaneous permanent regression of macroscopic tumours (Krikorian 1980). Of course for large values of c the probability of having a remission is large (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Since at present few malignant lymphomas are left untreated, we were obliged to go back to older publications to learn more about the occurrence of spontaneous remissions of these neoplasias. Although most such reports are anecdotal (details not shown) and extensive studies on this topic are lacking, the impression was gained that spontaneous regression of these neoplasias may not be extremely rare, could take place during viral infections and may have gone unnoticed (reviewed by Krikorian et al, 1980). Altogether, this scant information suggested that X ϭ approx.…”
Section: Discussionmentioning
confidence: 99%
“…Further, dNHLs rarely undergo localized ischemic necrosis and offer other advantages (Del Vecchio et al, 1991). To reduce the chance of cell emigration and immigration, which may falsify MI and AI, especially in generalized dNHL, we restricted the selected cases to stage I ϩ II (''localized'') disease according to the pathologic Ann Arbor classification (Carbone et al, 1971).Estimates for the value of X were based on the assumptions that most dNHLs are continuously growing neoplasias and that spontaneous lymphoma regression (Krikorian et al, 1980) is a rare event.The fraction of Ki-67 ϩ cells (Gerdes et al, 1993) also was assessed. In addition, we registered the percentages of cells immunoreactive for the bcl-2 protein, which counteracts apoptosis (Reed, 1994).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It can also take the form of palpable abdominal masses, which can be asymptomatic or can cause obstructive symptoms in the gastrointestinal or genitourinary tract. 3 Systemic complaints, or B symptoms, are reported in approximately 20% of patients with FL 4 and consist of fever, unexplained weight loss, and profuse night sweats. Considering the vagueness of symptoms or the lack of symptoms altogether, the variation in patients' presentation is considerable.…”
Section: Introductionmentioning
confidence: 99%